SQL programmer's reference - Bhamidipati, Kishore (Berkeley, CA : Osborne/McGraw-Hill, 1998)
SQL commands. Syntax flowcharts. Keywords and parameters.
Keywords: SQL; Database management; Database management; SQL (Computer program language) -- Handbooks, manuals, etc